Composite liquid crystal-polymer electrolytes in dye-sensitised solar cells: effects of mesophase alkyl chain length - Kamarudin, Muhammad Akmal; Khan, Ammar Ahmed; Said, Suhana Mohd; Qasim, Malik M.; Wilkinson, Timothy David (Taylor & Francis, 2018)
The doping of polymer electrolytes (PEs) with liquid crystal (LC) materials has been shown to improve the performance of dye-sensitised solar cells (DSSCs). This is achieved by promoting ionic conduction and increasing optical path length through multiple-light scattering within the photovoltaic devices. In LCs, it is well known that the length of the alkyl chain plays an important role since the LC morphology and mesophase stabilisation depend strongly on the alkyl group. In this work, liquid crystal-polymer composite electrolytes (LC-PEs) are prepared using nematic LCs with different alkyl chain lengths. The morphology of the LC-PEs is investigated and correlated with their electrical properties. Subsequently, DSSCs are prepared using the LC-PEs as a direct example of its application. It is shown that increasing the alkyl chain length of the LCs reduces the efficiency of the solar devices. The longer alkyl chains are speculated to intertwine, thus trapping the mobile ions and reducing the bulk ionic conductivity. For the same reason, longer alkyl chain LCs are thought to be unable to passivate the TiO2 surface through the adsorption of cyanobiphenyl groups and hence the higher probability of back recombination reaction between the electrons in TiO2 and PE.